A synergy of activity, stability, and inhibitor‐interaction of HIV‐1 protease mutants evolved under drug‐pressure. (22nd December 2020) - Khan, Shahid N.; Persons, John D.; Guerrero, Michel; Ilina, Tatiana V.; Oda, Masayuki; Ishima, Rieko
Abstract: A clinically‐relevant, drug‐resistant mutant of HIV‐1 protease (PR), termed Flap+(I54V) and containing L10I, G48V, I54V and V82A mutations, is known to produce significant changes in the entropy and enthalpy balance of drug‐PR interactions, compared to wild‐type PR. A similar mutant, Flap+(I54A), which evolves from Flap+(I54V) and contains the single change at residue 54 relative to Flap+(I54V), does not. Yet, how Flap+(I54A) behaves in solution is not known. To understand the molecular basis of V54A evolution, we compared nuclear magnetic resonance (NMR) spectroscopy, fluorescence spectroscopy, isothermal titration calorimetry, and enzymatic assay data from four PR proteins: PR (pWT), Flap+(I54V), Flap+(I54A), and Flap+(I54), a control mutant that contains only L10I, G48V and V82A mutations. Our data consistently show that selection to the smaller side chain at residue 54, not only decreases inhibitor affinity, but also restores the catalytic activity.